Parasites with zoonotic potential in canine fecal samples from Garanhuns, Pernambuco, Brazil - Macedo, Lucia Oliveira de; Santos, Marcos Antônio Bezerra; Santana, Breno Barros de; Pereira, Taylane Almeida; Silva, Naiara Mirelly Marinho da; Alves, Leucio Câmara; Ramos, Rafael Antonio Nascimento; Carvalho, Gílcia Aparecida de (Medicina Veterinária, 2020)
Among the gastrointestinal parasites of dogs that present public health importance, the species of the genus Ancylostoma and Toxocara are the most frequently detected, and have been important cause of soil contamination. The aim of this study was to detect gastrointestinal parasites in dog’s feces collected in households, streets and public squares of the city of Garanhuns, Pernambuco, Brazil. Fecal samples (n = 640) were collected in the environment and evaluated by parasitological methods of Willis-Mollay and Hoffman, Pons and Janer. Out of all samples, 51.09% (327/640) were positive for gastrointestinal parasites. In particular, in 70.94% (232/327) of the samples were detected eggs of Ancylostoma spp., and in 11.01% (36/327) coinfection by Ancylostoma spp. and Toxocara canis. In conclusion, the presence of eggs of zoonotic parasites in feces collected from the environment in the city of Garanhuns represent a risk for the transmission of Cutaneous Larva Migrans and Visceral Larva Migrans for the human population.